2008
DOI: 10.1016/j.drugpo.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Young Thai women who use methamphetamine: Intersection of sexual partnerships, drug use, and social networks

Abstract: Background-Given high rates of methamphetamine (MA) use among young people in Thailand and evidence of an association between MA and increased sexual risk behavior, we examined the association between women's recent sexual partnerships, social network characteristics and drug and alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…Their income sources were also strongly composed of illicit sources, further increasing likelihood of future incarceration, and they had fewer economic and health-related support resources within their networks. Recent studies have revealed high and understudied prevalence of poverty within the LGBT community, particularly among bisexual women 13 , and evidence of social network and support differences among sexual minority women 14 . There is a strong need to identify and address contributing factors to socioeconomic and social network marginalization among lesbian and bisexual women and a particular need to understand factors contributing to disproportionate engagement in illicit income generation activities which enhance risk for HIV and incarceration, especially sex exchange behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Their income sources were also strongly composed of illicit sources, further increasing likelihood of future incarceration, and they had fewer economic and health-related support resources within their networks. Recent studies have revealed high and understudied prevalence of poverty within the LGBT community, particularly among bisexual women 13 , and evidence of social network and support differences among sexual minority women 14 . There is a strong need to identify and address contributing factors to socioeconomic and social network marginalization among lesbian and bisexual women and a particular need to understand factors contributing to disproportionate engagement in illicit income generation activities which enhance risk for HIV and incarceration, especially sex exchange behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, conducting sexual network studies presents challenges with respect to sampling [10,11], subject protection [10], and data collection [10,12]. Previous sexual network studies were primarily limited to high-risk populations such as drug users, men who have sex with men, or individuals infected with HIV/STIs [13][14][15][16]. To fill this significant gap, we designed and conducted a cross-sectional study in a rural community in Yunnan Province to examine HIV prevalence, sexual behaviors, sexual networks, and drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Even in rural spaces it is possible to find such venues. 4 Moreover, it is largely appropriate for Thai men to frequent such places, even if they do not engage in direct sexual services-the sexually charged environment is fairly normalized in Northern Thailand even as more 'direct' commercial sex work venues (such as brothels) have been limited by an active HIV campaign over the past thirty years (German et al 2007). That government bureaucrats would find it completely normal to take a foreign researcher-who was studying the HIV epidemic-to such a place is nonetheless interesting; it is partially a function of the modern capitalist consumptive male subject that has developed alongside Thailand's growing economy over the past four decades (cf.…”
Section: Situating the Geographies Of Sex And Drugs In Thailand Soutmentioning
confidence: 98%
“…Put in another way, does a social geography of drug use and sex practices help better explain the terrains of subjectivity, power, and humannonhuman relations that mediate the everyday experiences of those whose lives are so intimately affected by these practices? It is clear, actually, that drug use and sex practices are often interconnected and this has a tremendous impact on the processes of subjectivity (Malins 2004) as well as on the sexual health of various populations (Allen et al 2003;German et al 2007;Limanonda 2003). Indeed, in places such as Thailand, which has recently seen a slow rise in the rate of HIV among key cohorts of both men and women (National AIDS Prevention and Alleviation Committee 2010), it is critical for geographers to understand the complex interrelationships between drug use and sex practices in the context of the discursive framings of sexual (ill) health (cf.…”
Section: Introductionmentioning
confidence: 98%